Performance of weanling pigs as influenced by feeding insect-and fungal-damaged grain sorghum - Dietz, J.C.; Behnke, Keith C.; Allee, G.A.; Deyoe, C.W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Using 128 crossbred pigs with an average initial weight of 18.3 Kg, we determined the effect that insect- and fungal-damaged sorghum would have on the pigs' performance. No differences were found in daily feed consumption for any treatment during a 28-day feeding trial. Average daily gains and feed efficiencies were similar to those of the control for pigs fed grain sorghum that had been damaged by lesser grain borer; red beetle; a mixture of lesser grain borer, flat grain beetle, and indian meal moth, or Aspergilas Candidus. Pigs fed grain sorghum damaged by rice weevil showed lower average daily gains and a higher feed-to-gain ratio than did the controls. Aspergilas Glaucus-damaged grain showed similar ADG, but a significantly poorer F/G during the first 14 days, but not during the second half of the study. Even though insect damaged grain appears to be nutritionally adequate rather significant losses of dry matter and energy are sustained when grain sorghum is allowed to go out of condition. Up to 6% of the gross energy and approximately 5% of the crude protein content was lost to infestation or fungal invasion.
Keywords: Swine; Performance; Insect and fungal damaged grain sorghum; Weanling pigs